Nationalepen zwischen Fakten und Fiktionen - Detering, Heinrich (Humaniora: Germanistica, 2011)
Since the 19th century national epics have had an important function in the cultural scene of almost every nation, and the same is true for the Central and East European countries that have regained their independence after 1989. The programmatic national epic was brought to life by the German Romanticism, especially by writers such as Jacob and Wilhelm Grimm. The contributions in this volume analyse the development, relationship, and reception of European national epics. They rely on a wide concept of epic and offer studies on various texts, such as the Icelandic sagas, the "Nibelungenlied", the "Poems of Ossian", the "Kinder- und Hausmärchen" of the Grimm brothers, Schiller's "Wilhelm Tell", Božena Němcová's "Babička", Esaias Tegnér's verse epic "Frit(h)iofs saga", the Finnish national epic "Kalevala" and the Estonian national epic "Kalevipoeg".